Clementis Alexandrini Protrepticus - Clement, of Alexandria, Saint, approximately 150-approximately 215. (Vigiliae Christianae, Supplements, 1995)
Clement of Alexandria (ca A.D. 150-215) is one of the leading Church Fathers and the first Christian philosopher. His early Protrepticus is of great significance for Patristics, Classical scholarship, Greek philosophy and religion. The treatise is preserved virtually in a single manuscript --the famous Codex Arethae, Parisinus graecus 451, copied in 913-914,-- which proves to be lacunose, corrupt, interpolated and dislocated. The only critical edition of the Protrepticus was prepared back in 1905 by Otto Stählin (G.C.S., Volume 12). The present edition is based on a thorough in-depth study of the Parisinus, on the inclusion of the entire opus of Clement, on an extended and updated Quellenforschung , and finally, on a more sensitive approach to meaning and textual criticism. The edition includes the Scholia .